Environmental monitoring of natural waters in the zone of impact of an enterprise producing explosives. Issue 1 (October 2020) - Patokin, Dmitry; Danilov, Alexander; Isakov, Alexander
Abstract: Production of explosives, as part of chemical industry, has a significant anthropogenic impact on components of environment. The greatest negative impact due to water requirements of the industry enterprises have on hydrosphere. Generally pollutants of this group of enterprises are nitroesters – one of the most important components of products that determine energy properties of powders. In article considers the need for water quality monitoring of water bodies located in zone of influence of enterprises for contamination with nitroesters, in particular nitroglycerine (1, 2, 3-trinitrooxypropane). As a rule, such enterprises are located on the largest water bodies. Low solubility of the substance in water determines its risk to aquatic organisms and population. The Kama river was selected as the water object of the research in area of impact of the gunpowder production enterprise on territory of a large industrial and residential agglomeration of Perm. According to the results of environmental monitoring, which consisted in sewage and natural water, a significant excess of maximum permissible concentration of nitroglycerin in natural waters was detected, which is unacceptable for water bodies of the highest fishing category of water consumption. To reduce the anthropogenic impact on the water body, it is proposed to introduce a system for wastewater treatment from the source pollutant by ozonation of industrial wastewater with introduction of an alkaline reagent. The revealed high efficiency of the method of wastewater treatment to the content of nitroester at level of trace concentrations makes it possible to exclude the impact of the enterprise on the watercourse.